Antioxidant Activity of Lupine Seeds in Nile Tilapia Fish (O. niloticus) Suspected to Oxidative Stress Induced by Neemazal T/S - El-Badawi, Ashraf A. (International Journal of Applied Sciences and Biotechnology, 2015)
This study was designed to determine the effects of acute toxicity of NeemAzal T/S on Nile tilapia (Oreochromis niloticus) and to investigate the antioxidant effect of Lupine seeds on the gills and erythrocytes(EC) oxidative stress induced by NeemAzal T/S in Nile tilapia .Two doses of NeemAzal; 1/10 LC50:16 PPM (NA1) and 1/5 LC50:32 PPM (NA2) and three periods of 10, 20 and 30 days were used. Oxidative stress parameter, total peroxide (TP) and antioxidant enzyme activities, catalase (CAT) and superoxide dismutase (SOD) as well as glycemia were measured. NA2 markedly decreased CAT and SOD activities in gills and erythrocytes at most periods, but NA1 had less effect. In turn, both doses significantly enhanced TP levels in gills and EC. Moreover, hyperglycemia was detected 30 days after control (NA) exposure. LS significantly curtailed or abolished the adverse effect of NA exposure on oxidative and antioxidant parameters in gills and EC. This may be attributed to the hypoglycemic effect of LS as well as its antioxidant efficiency. In conclusion, Lupine seed exerts a potent antioxidant activity against oxidative damages induced by NeemAzal T/S in Nil tilapia fish. Int J Appl Sci Biotechnol, Vol 3(2): 170-178 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12284